Anfangsjahre der Berlin-Krise (Herbst 1958 bis Herbst 1960) - Wettig, Gerhard (Quellen und Darstellungen zur Zeitgeschichte, 2015)
Published for the first time, Khrushchev`s secret conversations, consultations, and notes during the early phase of the Berlin Crisis that he initiated show us a politician filled with strong emotions who aimed at the domination of West Berlin and the ruin of NATO, thereby openly challenging the Western powers. However, he was not ultimately prepared to risk the nuclear war he had threatened.